Nepali Text to Speech Synthesis System using FreeTTS - Shah, Krishna Bikram; Chaudhary, Kiran Kumar; Ghimire, Ashmita (SCITECH Nepal, 2018)
This paper confers the tools and methodology used in developing a Nepali Text to Speech Synthesis System using FreeTTS and is entirely developed in Java and uses FreeTTS synthesize1: Vocalized form of human communication is Speech. Here the Nepali Language is Synthetized based on formant approach and the use of one of the popular generic frameworks FreeTTS that is available in public domain for the development of a TTS system. The Text To Speech Architecture has been developed putting more emphasis on the Natural Language Processing (NLP) component rather than Digital Signal Processing (DSP) component. Nepali language being mostly used language in Nepal and some parts of India and abroad, a text-to-speech (TTS} synthesizer for this language will prove to be a convenient tool and communication technology (JCT) based system to aid to those majorities of people who are illiterate and also to those who are physical impairments like visually handicapped and vocally disabled persons. This ability to convert text to voice may reduce the dependency, frustration, and sense of helplessness of these people. The system can be extended to include more features such as emotions, improved tokenization, interactive options and the use of minimal database.